Controlled surface/interface structure and spin enabled superior properties and biocompatibility of cobalt ferrite nanoparticles - Ansari, Sumayya M.; Sinha, Bhavesh B.; Pai, Kalpana R.; Bhat, Suresh K.; Ma, Yuan-Ron; Sen, Debasis; Kolekar, Yesh D.; Ramana, C., V. (Allied Surface Science, 2018)
High quality, crystalline, well-dispersed, and stable magnetic oxide nanoparticles (NPs) of inverse spinel cobalt ferrite (CoFe2O4; CFO) were prepared by a facile, reproducible, and simple hydrothermal route. The transmission electron microscopy, small-angle scattering and X-ray diffraction analyses demonstrate the structural quality of CFO NPs with a controlled size of similar to 12 nm. Small-angle scattering experiments demonstrate that the pristine CFO NPs have the individual size similar to 8.5 nm and spherical shape. The Raman and infrared spectroscopic measurements further confirm their high chemical quality and cubic symmetry. CFO NPs exhibit a remarkable, maximum coercivity (H-c) value of 18.92 kOe, which is the highest value achieved to date. Surface spins and spins canting along with a weak dipolar interaction accounts for the giant H-c and large effective anisotropy (11.45 x 10(6) erg/cm(3)) of these CFO NPs. The magnetic grain size of NPs reveals that the canted surface spins exist around the magnetic particles. Reorientation of surface spins and interparticle interaction causes the jumping behaviour in M-H hysteresis loops at H = 0. The cell viability of CFO NPs against the cancer (cisplatin resistant ovarian cancer - A2780/CP70) was evaluated to determine their potential application in biomedicine and health science. The mild response of CFO NPs in terms of their anti-proliferative nature against cancer cells and negligible cytotoxicity suggests their human-safe-and-friendly nature which makes them suitable for biomedical/health-related applications. Assessment of toxicity toward human red blood cells (RBC) revealed that hemolysis is less than 5% compared to the positive control confirming the potential applications of CFO NPs targeting human cells and making relevant for adopting them in biomedicine.

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.